Development Strategy of Tourism Village in Belimbing Village, Pupuan District, Tabanan Regency - DHARMAWAN, I MADE ADI; SARJANA, I MADE; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.1, Januari 2014, 2014)
The aims of study are to carry out the potential of Belimbing Village which is seen from four aspects those are Strength, Weakness, Opportunity, and Threat, and also to know the strategy of development of rural tourism in Belimbing Village. This study based on quantitative and qualitative method. Quantitative data was directly from observations and interviews with the questionnaires  besides, the supporting data was from library resource. Based on analysis result, Internal factors (a) strength : beautiful and conservation of nature are the most significant influence on the development of rural tourism in Belimbing Village, (b) Weakness : Belimbing village is not ready to receive the tourists, since the lack quality of the environmental cleanliness. External Factors (a) opportunity : the most important factor of opportunity is the value of the people who always maintain and preserve traditional cultural, (b) Threat : the most important threat is the threat of competition with others regions in the development of rural tourism. Based on SWOT analysis obtained the development strategy such as follows; (a) S-O strategy is the development of rural tourism in order to maintain the attraction and promotion in Belimbing village. (b) W-O Strategy is to improve the facilities and infrastructure, (c) S-T strategy is outreach to the local people, in order to increase security and defense, (d) W-T strategy is the strategy of administration and management of Belimbing village as well as language training and tour guiding to the local people. Therefore, the priority that can be done in developing rural tourism and to maintain its attraction by providing tourism packages or tracking map and also to order the local are properly.   Keyword : potential, SWOT analysis, tourism village
Keywords: potential; SWOT analysis; tourism village